Factors Contributing to African Women’ Success in the Diaspora - Maganda, Dainess M. (Advances in Social Sciences Research Journal, 2021)
Gender plays a vital role in different aspects of development. Much research on women empowerment and economic development has focused on the disparity between male and female, especially the salaries they receive and some focus on women not equally contributing economically to their societies. Scholars agree that women contribute greatly to their family’ economic development. Through a questionnaire involving 20 African women from more than 5 African countries who currently reside in America and England, this study explores factors which contribute to their academic and professional success in the diaspora. Data seems to suggest that family support, modification of gender roles, and faith contribute to the academic and professional success of African women outside of Africa. The study shows the need to transcend cultural norms regarding gender roles to ensure women’ success in their professions wherever they reside, thus enabling them to make a sound contribution to their families’ and communities’ economic development.